Atal Bihari Vajpayee: Beacon for new India - Hari, D.K.; Hari , D.K. Hema (New Delhi Bharath Gyan Series, 2019)
This book throws light on the Beacon of New India. A great leader, who showed the path to New India and defined what New India should be all about. A leader, who bridged the time window from Independent India to New India. A leader, who founded the largest political party of India and was sworn in thrice, as the Prime Minister of India. A leader, who had firmly balanced traditionalism, humanism, idealism, poetry, and politics with statesmanship in Governance. A leader, who threw light on the changes to be done within India, to change its image outside India. A leader, who worked from Inside Out. A (3z(BConsensus Colossus(3y (Bin consensus. He was a prequel to New India. And, so is this book, to Knowing New India.s
Keywords: Prime Minister; Indian Politics; Atal Bihari Vajpayee